Common α-Fuzzy Fixed Point Results with Applications to Volterra Integral Inclusions - Abdullah Eqal Al-Mazrooei; Jamshaid Ahmad (Journal of Mathematics)
The purpose of this paper is to establish some common α-fuzzy fixed point theorems for a pair fuzzy mappings and obtain some results of literature for multivalued mappings. For it, we define the notion of generalized Θ-contractions in the context of b-metric spaces. As applications, we investigate the solutions of Volterra integral inclusions by our established results.